Loading and Release of Charged and Neutral Fluorescent Dyes into and from Mesoporous Materials: A Key Role for Sensing Applications - Climent, Estela (Micromachines (Basel), 2021)
The aim of this study is to determine the efficiency of loading and release of several zwitterionic, neutral, anionic and cationic dyes into/from mesoporous nanoparticles to find the optimum loading and release conditions for their application in detection protocols. The loading is carried out for MCM-41 type silica supports suspended in phosphate-buffered saline (PBS) buffer (pH 7.4) or in acetonitrile, involving the dyes (rhodamine B chloride, rhodamine 101 chloride, rhodamine 101 perchlorate, rhodamine 101 inner salt, meso-(4-hydroxyphenyl)-boron–dipyrromethene (BODIPY), sulforhodamine B sodium salt and fluorescein 27). As a general trend, rhodamine-based dyes are loaded with higher efficiency, when compared with BODIPY and fluorescein dyes. Between the rhodamine-based dyes, their charge and the solvent in which the loading process is carried out play important roles for the amount of cargo that can be loaded into the materials. The delivery experiments carried out in PBS buffer at pH 7.4 reveal for all the materials that anionic dyes are more efficiently released compared to their neutral or cationic counterparts. The overall best performance is achieved with the negatively charged sulforhodamine B dye in acetonitrile. This material also shows a high delivery degree in PBS buffer.